Disclosure of climate risk information by the worlds largest companies - Kouloukoui, Daniel (2018)
The risks related to global climate change are seen as threats to companies, taking into consideration their impact on the return on investment. In order to mitigate climate risk and introduce new opportunities to financiers, companies need to identify, manage, and report climate risks. The purpose of this paper is to investigate the climate risks disclosed by the 100 largest companies in the world, according to the Bloomberg and Price Waterhouse Coopers (PwC 2015) classification, and identify some characteristics of these companies that explain the disclosure level of such information. Preliminary results revealed that of the companies investigated, 14% did not disclose any climate risk information in the Carbon Disclosure Program (CDP) report. Also, from the companies that disclosed information according to the Global Reporting Initiative (GRI), 9.9% did not provide information regarding policies, actions, and strategies for mitigating the risks related to climate change. The results shown by the content analysis suggested that, in general, there is still a low level of disclosure about climate risks by these companies. The final results through econometric instruments and statistical tests indicate that the size of the company or the fact that corporations are from developed countries do not necessarily explain the level of information disclosed. However, the activity sector, the continent, and the efficiency of the Board of Directors are factors that strongly explain the level of climate risk disclosure. We conclude that more effort is needed to encouragean engaging attitude fromcorporations to developactions,policies,andstrategiesto mitigate climate change risks and threats. In addition, the world’s largest companies should make a greater investment in climate risk disclosure.